Pay dirt - Paretsky, Sara (Paretsky, Sara. V.I. Warshawski novel, 2024)
While visiting Angela, one her protégées in Kansas, V.I. Warshawski, when Angela's roommate goes missing and V.I. finds her near death in a drug house, is pitched headlong into the country's opioid crisis and a local land-use battle with roots going back to the Civil War.